2019
DOI: 10.3390/ijerph16101771
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of the Elderly and Its Influence on Their Activities of Daily Living in Shangrao, Jiangxi Province

Abstract: To investigate the activities of daily living (ADL) and influencing factors, this survey study was conducted in Shangrao of Jiangxi. A total of 1087 elderly subjects in a long-term care (LTC) program participated in this study and their physical function, cognitive ability, self-rated health, and chronic disease were recorded during March 2017 and April 2018. The ADL scale was used to evaluate the health status of the elderly. F-test and multiple linear regression showed that the average ADL of the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…In a study conducted by Xu et al the cognitive ability was significantly associated with seniors who had poor ADL outcomes. 9 The same was the case in a Brazilian study by Virtuoso Júnior, wherein, functional disability in both BADL and IADL was significantly associated with cognitive deficits. 14 A recent systematic review by Lindberg et al indicated that individuals with mild cognitive impairment displayed significantly greater IADL impairment than cognitively intact controls.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In a study conducted by Xu et al the cognitive ability was significantly associated with seniors who had poor ADL outcomes. 9 The same was the case in a Brazilian study by Virtuoso Júnior, wherein, functional disability in both BADL and IADL was significantly associated with cognitive deficits. 14 A recent systematic review by Lindberg et al indicated that individuals with mild cognitive impairment displayed significantly greater IADL impairment than cognitively intact controls.…”
Section: Discussionmentioning
confidence: 58%
“…In a study conducted in the Shangrao city in Jiangxi province in China, older age, poor self-rated health, cognitive impairment and visual impairment were found to be associated with poor ADL outcomes. 9 In a study from Brazil, functional disability in BADL was found to be associated with age, falls, alcohol consumption, number of drugs and cognitive deficits among others while in IADL, functional disability was significantly associated with age, family arrangement, and number of drugs, alcohol consumption and cognitive deficit among others. 14 In a review, unintentional weight loss was reported as a predictor of functional disability in elderly people.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though the study adjusted for many variables relevant for P-ADL function, the analysis did not include information about education. Some previous studies have shown that educational background has an impact on P-ADL function [68][69][70]. However, to our knowledge, there is only one study that has explored this association among people with dementia [28], and this study did not find education to have a significant impact on P-ADL.…”
Section: Discussionmentioning
confidence: 64%
“…Polymorbidities in the elderly were associated with functional dependence to BADL and IADL in a national study 38 as well as among the Japanese, 39 the Americans, 40 the Dutch, 41 and Europeans and Israelis, 4 implying the impact of chronic diseases over the functional capacity of elderly. The progressive decline in physiological reserves during biological aging contributes to the increased risk for several diseases, 42 which can directly affect the biopsychosocial well-being of the elderly, according to the limits of their adaptation ability.…”
Section: Ourmentioning
confidence: 95%